Philanthropic giving, sales growth, and tourism firm performance: An empirical test of a theoretical assumption. Issue 6 (September 2019) - Wang, Keling; Miao, Yaqiong; Chen, Ming-Hsiang; Hu, Dengfeng
Aiming to test a theoretical assumption that corporate giving (CG) could increase sales of tourism firms and hence firm performance, this study empirically investigates whether CG could increase sales growth and enhance firm performance in the Chinese tourism industry. Empirical results can enhance theoretical innovation and development. Panel regression test results reveal three interesting findings and support the theoretical assumption. First, there is a variation in the impact of CG on tourism firm performance. While CG does not significantly affect Chinese travel firm performance, it has a significant effect on hotel firm performance in terms of sales growth, return on asset, and return on equity. Second, state ownership is not a critical factor in the financial impact of CG on travel and hotel firms. Third, the Chinese hotel industry might use CG a short-term image builder and sales and profitability generator rather than as a long-term competitiveness strategy. Lastly, there is an inverted U-shaped relationship between CG and hotel firm performance.